Baseline study in environmental risk assessment: Escalating need for computer models to be whole-system approach. Issue 5 (4th March 2017) - Butt, T. E.; Gouda, H. M.; Alam, A.; Javadi, A. A.; Nunns, M. A.; Allen, T. J.
ABSTRACT: Despite landfills having the potential to pollute the environment both during their operation and long after they have ceased to receive waste, they remain a dominant waste management option, particularly in the UK. In order to combat the environmental pollution caused by landfills, risk analysis is increasingly being employed through computer models. However, for a risk analysis process to be successful, its foundation has to be well established through a baseline study. This paper aims to identify knowledge gaps in software packages regarding environmental risk assessments in general, and especially those that have been developed specifically for landfills and landfill leachate. The research establishes that there is no holistic computer model for the baseline study of landfills, which risk assessors can use to conduct risk analyses specifically for landfill leachate. This paper also describes a number of factors and features that should be added to the baseline study system in order to render it more integrated—thereby enhancing quantitative risk analysis, and subsequently environmental risk management.